Multiultural Education Studies In The Perspective Of Sociology Of Education - Asep Mulyana; Rahmat Al Bayan; Midun Sopan; Feri Hardiyanto (International Journal of Social Research, 2023)
Indonesia is a multicultural nation with a high level of pluralism. This can be a potential for national progress as well as its decline, depending on the quality of heterogeneity management. Therefore, an understanding of the nation's motto "unity in diversity" must be instilled in the younger generation from an early age so that they are able to play a role in maintaining unity in the midst of national diversity. One of the efforts that can be realized in order to respond to this problem is to understand the study of multicultural education or the concept of multicultural education (multicultural education) and its approach in education in Indonesia. Thus, multicultural education as part of character education will have a greater chance of succeeding.